PERANCANGAN LANSKAP KEBUN PERCOBAAN SINDANG BARANG SEBAGAI SARANA AGROWIDYAWISATA - Fauzan Muhamad Fahrudin; Akhmad Arifin Hadi (Jurnal Lanskap Indonesia, 2013)
ABSTRACTSindang Barang Experimental Field (KPSB) is one of a supporting facilities for research, education, and community service. KPSB is one of University Farm (UF) of IPB, with total area 78 750 m2, consist of planting Bloks, research garden, building, and supporting facilities. Recently, KPSB is not used optimally and and not put in good use due to lack of facilities. Therefore, landscape design of KPSB is needed as a reference for future development of KPSB. The purpose of this study is designing an experimental field with techno-ecologycal farming concept. This research used survey and descriptive method with the design phase approach followed Bell (2008). The main design concept is techno-ecological agro tourism. This design was not only concern about research and education activities, but also how to support agro tourism. The zoning in this design are: welcome area (9%), agriculture (27%), education (23%), livestock (11%), talun (20%), and tourism (10%). In the future, it is expected that agrotourism activities can be done well on KPSB.Keywords: agro-tourism, experimental field, landscape design